Assessment of Safety and Therapeutic Efficacy of Rosa damascena L. and Quercus infectoria on Cardiovascular Performance of Normal and Hyperlipidemic Rabbits: Physiologically Based Approach - Siyavash Joukar; Masoumeh Askarzadeh; Beydolah Shahouzehi; Hamid Najafipour; Hossein Fathpour (Journal of Toxicology)
According to the use of Quercus infectoria (QI) and Rosa damascena L. (RD) for therapeutic purposes and lack of adequate information about their cardiovascular effects, we investigated the cardiovascular indices of rabbits which chronically pretreated with these agents. Animal groups were control group (CTL), RD and QI groups with normal chow plus 1.5 g RD and QI extracts, respectively, in each kg of the diet for 45 days; Hyperlipidemic (H) group received high-fat diet for 45 days; H+RD and H+QI groups received high fat diet plus QI and RD extracts, respectively. Blood pressure was greater in H+RD group than CTL, RD, and H groups. Left ventricular developed pressure and left ventricular systolic pressure increased significantly in H+RD group versus CTL and RD groups ( and , resp.) and in H+QI groups ( versus QI groups). Left ventricular end diastolic pressure (LVEDP) showed significant reduction in H+QI group versus H group. QI attenuated the values of total cholesterol, LDL, TG, and atherogenic indices of plasma when coadministrated with a high-fat diet. The results suggest the antilipidemic and antiatherogenic effects of QI. In addition, the use of RD along with a high-fat diet may increase the risk of hypertension in rabbits.